Psychological Flexibility Among Competitive Athletes: A Psychometric Investigation of a New Scale - Johles, Lis (Front Sports Act Living, 2020)
There is increasing interest in applying acceptance and mindfulness interventions among athletes. However, there is a lack of sport-specific psychometrically evaluated scales to measure the impact of these interventions. The present study describes the development of a measure: the Psychological Flexibility in Sport Scale (PFSS). Its validity was tested in two studies. In the first study, with 152 elite athletes from various sports, explorative factor analysis was used to evaluate the scale's validity, and one factor emerged with seven items. Significant correlations between psychological flexibility, performance, and quality of life were found. Moreover, the PFSS was significantly negatively associated with age, number of years in sport, and number of years as an elite athlete. In the second study, the confirmatory factor analysis with a new population (252 athletes) supported the one-factor solution. Further, positive associations were found with anxiety (BAI) and depression (BDI-I), indicating construct validity. In conclusion, this study presents a scale for measuring psychological flexibility in a broad range of athletes, with satisfactory psychometric properties and the potential to be a useful instrument for both researchers and clinicians in the sport field.